The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1159/000477487
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Features of the Large Cell Variant of Small Cell Ovarian Carcinoma in Young Patients with Hypercalcemia: Histological Findings and Review of the Literature

Abstract: Objective: To present the cytological features of a very rare and lethal ovarian neoplasm occurring in the young. Study Design: We reviewed the cytological findings as they presented in touch imprints obtained from an ovarian mass sent to our department for frozen section investigation. Results: Smears were highly cellular. The cells were of intermediate size with a moderate amount of microvacuolated, pale, or eosinophilic cytoplasm with indistinct cell borders. The nuclei were of round or oval shape with mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Only three articles 20–22 we found in the literature described large cell ovarian carcinomas with similar features to the current case, the first one diagnosed on a peritoneal washing like in our case with marked cytologic similarities. However, their immunohistochemical features were different from the case here reported and none had concurrent molecular pathologic study; moreover, hypercalcemia was found only in 1/3 cases.…”
Section: Discussionsupporting
confidence: 68%
“…Only three articles 20–22 we found in the literature described large cell ovarian carcinomas with similar features to the current case, the first one diagnosed on a peritoneal washing like in our case with marked cytologic similarities. However, their immunohistochemical features were different from the case here reported and none had concurrent molecular pathologic study; moreover, hypercalcemia was found only in 1/3 cases.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, in the present report, cytomorphologic features of SCCOPT metastatic to cervix, on Papanicolaou stained, SurePath preparation have also been highlighted. There are only occasional case reports wherein cytological features of SCCO have been presented, mainly of the hypercalcemic type; [16][17][18][19][20] with only a few diagnosed primarily on exfoliative cytology. 21,22 We believe ours is the first report of a SCCOPT being diagnosed by FNAC, supplemented with ICC on cellblock.…”
Section: Discussionmentioning
confidence: 99%
“…In the peritoneal fluid, SCCOHT presents as loosely cohesive neoplastic cells with large hyperchromatic nuclei with prominent nucleoli [85]. The nuclei may show mild to moderate atypia, with occasional grooving and intranuclear inclusions [86]. The cytoplasm varies from scarce to moderately abundant with dark, granular appearance to brightly eosinophilic with hyaline globule, imparting a rhabdoid morphology [85].…”
Section: Seromucinous Neoplasmsmentioning
confidence: 99%